2011
DOI: 10.1007/s10964-011-9712-0
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effects of Aggression on the Associations Between Social Withdrawal Subtypes and Peer Difficulties During Early Adolescence

Abstract: Recent research has revealed significant heterogeneity in the peer difficulties associated with social withdrawal subtypes during early adolescence, but little is known about possible sources of that heterogeneity. This study of 194 Indian young adolescents (48% female; 90% Hindu; M age= 13.35 years) evaluated whether the peer adversity related to self-reported social withdrawal subtypes (shyness, unsociability, avoidance) varied as a function of peer-nominated overt and relational aggression, and gender. Regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…To our knowledge, one study directly examined a moderator between unsociability and adjustment. Bowker, Markovic, et al (2012) reported a protective effect of relational aggression on the relation between unsociability and peer victimization. Our study provided additional evidence of moderating factors in these kinds of associations, in a sample of Chinese children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, one study directly examined a moderator between unsociability and adjustment. Bowker, Markovic, et al (2012) reported a protective effect of relational aggression on the relation between unsociability and peer victimization. Our study provided additional evidence of moderating factors in these kinds of associations, in a sample of Chinese children.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one study has examined moderators in these associations. Bowker, Markovic, Cogswell, and Raja () reported that unsociability was a positive predictor of peer victimization at medium and low levels of relational aggression, but not at high levels. That is, unexpectedly, relational aggression appeared to be a protective factor for unsociable children.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Social withdrawal, the behavior of consistently withdrawing oneself from the peer group (Rubin & Coplan, 2004), has been linked with such internalizing difficulties as anxiety and depression in childhood and adolescence (see Rubin & Coplan, 2010, for a review). Despite these findings, the risks associated with withdrawal may depend on the underlying motivations; different outcomes have been found for youth with differing combinations of social approach and social avoidance motivations (Bowker & Raja, 2011; Bowker, Markovic, Cogswell, & Raja, 2012; Thijs, Koomen, de Jong, van der Leij, & van Leeuwen, 2004). Shyness consists of high approach and high avoidance motivations (Asendorpf, 1990; 1993); shy youth are interested in interacting with others but withdraw because they are socially anxious.…”
mentioning
confidence: 97%
“…Coplan et al (2012) found that low approach motivation was associated with socially withdrawn behaviors in young adolescents, which in turn predicted peer difficulties. Bowker and colleagues (2011; 2012) found that both unsociability and avoidance were associated with peer rejection in young adolescents. Because researchers have yet to examine preference-for-solitude beyond early adolescence, however, it is not known whether preference-for-solitude is maladaptive across adolescence.…”
mentioning
confidence: 99%